Differential Type 1 IFN Gene Expression in CD14+ Placenta Cells Elicited by Zika Virus Infection During Pregnancy - Haese, Nicole N.; Smith, Hannah; Onwuzu, Kosiso; Kreklywich, Craig N.; Smith, Jessica L.; Denton, Michael; Kreklywich, Nicholas; Streblow, Aaron D.; Frias, Antonio E.; Morgan, Terry K.; Hirsch, Alec J.; Bimber, Benjamin N.; et al. (Frontiers in Virology, 2021)
Zika virus (ZIKV) is an arthropod-borne Flavivirus that can also be transmitted vertically from infected mother to fetus. Infection of the fetus during pregnancy can lead to congenital malformations and severely impact fetal brain development causing a myriad of diseases now labeled Congenital Zika Syndrome (CZS). The mechanisms by which ZIKV crosses the placenta into the fetal circulation and the extent of ZIKV-induced changes remain unclear. We have previously shown that ZIKV infection of pregnant rhesus macaques results in abnormal oxygen transport across the placenta which may promote uterine vasculitis and placental villous damage. Changes in immune cell frequencies and activation status were also detected, as were distinct changes in the proportions of CD14+ cell subsets with an altered ratio of classical to non-classical CD14+ monocyte cells in both the maternal decidua and placental villous from ZIKV-infected animals compare to uninfected controls. In the current study, we performed single cell RNA sequencing on CD14+ cells isolated from the villous of animals that were ZIKV infected at 31, 51, or 115 days gestation (term is ~168 days) compared to pregnant, time-matched uninfected controls. Bioinformatic analysis identified unique transcriptional phenotypes between CD14+ cells of infected and uninfected animals suggesting a distinct and sustained difference in transcriptomes between infected and uninfected CD14+ cells derived from the decidua. The timing of ZIKV infection had no effect on the CD14+ cell transcriptional profiles. Interestingly, ZIKV infection caused changes in expression of genes in pathways related to cellular stress and metabolism as well as immune response activation. Type 1 interferon response genes (ISGs) were among those that were differentially expressed following infection and these included members of the ISG12 family, IFI27 and IFI6. These ISGs have been recently described as effectors of the IFN response to flaviviruses. Supplementing our animal findings, in CD14+ cells isolated from human placenta, ZIKV infection similarly induced the expression of IFI27 and IFI6. Overall, our results showed that ZIKV infection during pregnancy induces the stable expression of antiviral genes within CD14+ cells of the placenta, which may provide an immune shield to protect the placenta from further infection and damage.